(untitled) (Bangladesh Journal of Urology, 2020)
Objectives: To review the outcomes of modification of groin lymph nodes dissection on morbidity from surgical treatment of a patient with penile cancer and to find out accurate treatment plan according to stages of the primary lesion from current literatures. Methods: We searched the pubmed database for English Language published in the past for years using incidence, etiology, pathology, clinical presentation, staging and management of penile cancer. Result: From retrieved literatures better understanding of pathologic features allow for stratification of patients into low, intermediate, or high risk for lymph node involvement. Lymphatic mapping to this stratification improves selection of patients who might benefit from lymph node dissection after excision of the primary lesion. The recent use of a modified lymph node dissection has minimized morbidity. Current chemotherapy agents are ineffective in this disease. Conclusion: Patholoigc features of the primary lesion and the incorporation of lymphatic mapping have improved the selection of patients who might benefit from lymph node dissection. The use of a modified lymph node dissection in selection patients has decreased morbidity. Effective chemotherapy agents are needed in the management of advanced penile cancer. Bangladesh Journal of Urology, Vol. 15, No. 2, July 2012 p.48-55